Association of serum triglycerides levels with severity and prognosis of acute ischemic stroke - سعيد هالة; سلمان ربا; الحريري نورس (Latakia University Journal -Medical Sciences Series, 2022)
Background: Serum lipid levels have been investigated as prognostic markers in patients with acute ischemic stroke. However, these results remain inconsistent. This study aimed at assessing the Association of serum triglycerides levels with severity and prognosis of acute ischemic stroke. methods: Our study included 125 first-ever acute ischemic stroke patients. Serum triglyceride level was measured within 48 hours after stroke onset. Stroke severity on admission was assessed using Scandinavian Stroke Scale (SSS). The patients were divided into 2 groups: those with severe stroke (SSS ≤ 25) and those with mild/moderate stroke (SSS< 25). All participants were assessed at 3 months after stroke using the modified Rankin Scale. Results: Patients with severe stroke had significantly lower serum triglyceride level than patients with mild/moderate stroke (±134.656.2 mg/dl versus ±206.863.9 mg/dl) p-value0.001>. After adjusting for age, sex, atrial fibrillation, diabetes mellitus, and ischemic heart disease, patients with triglyceride <200mg/dl had lower risk of severe stroke than those with triglyceride >200 mg/dl (OR: 6.23 CI: 1.22 to 20.17).Patients with bad prognosis had significantly lower serum triglyceride level than patients with good prognosis (±138.751.7 mg/dl versus ±214.862.3mg/dl) p-value0.001> Conclusions: Our results suggest that lower level of triglyceride is associated with the more severe stroke and bad prognosis.